2012
DOI: 10.1074/jbc.m112.401208
|View full text |Cite
|
Sign up to set email alerts
|

Specific Function of the Met-Tyr-Trp Adduct Radical and Residues Arg-418 and Asp-137 in the Atypical Catalase Reaction of Catalase-Peroxidase KatG

Abstract: Background: Catalase activity in catalase-peroxidases occurs through a poorly defined mechanism requiring residues Arg-418, Asp-137, and the amino acid adduct (M 255 Y 229 W 107 ). Results: Along with an adduct radical, Arg-418 stimulates O 2 release from dioxyheme, the rapid formation of which requires Asp-137. Conclusion:The electronics of the Arg-418:MYW-radical interaction enables discharge of O 2 during H 2 O 2 turnover. Significance: An atypical catalase mechanism operates in KatG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…On the basis of these results, we were able to put forward a model of the enzymatic activity in which we postulated the formation of two Cpd I species, one of which is capable of peroxidatic activity, the other of catalytic activity. Importantly, the radical adduct species has been characterized spectroscopically very recently [ 110 ]. The peculiar properties of the M-Y-W adduct, specifically its low ionization potential when Tyr238 is unprotonated, have been proposed to be responsible for O 2 activation by KatG [ 111 ].…”
Section: Qm/mm Applications To the Study Of Enzymatic Reactivity Amentioning
confidence: 99%
“…On the basis of these results, we were able to put forward a model of the enzymatic activity in which we postulated the formation of two Cpd I species, one of which is capable of peroxidatic activity, the other of catalytic activity. Importantly, the radical adduct species has been characterized spectroscopically very recently [ 110 ]. The peculiar properties of the M-Y-W adduct, specifically its low ionization potential when Tyr238 is unprotonated, have been proposed to be responsible for O 2 activation by KatG [ 111 ].…”
Section: Qm/mm Applications To the Study Of Enzymatic Reactivity Amentioning
confidence: 99%
“…The X-ray structures revealed that KatGs possess unique covalent bonds formed among the side chains of three distal residues, Met-Tyr-Trp, which are located on the distal side of the haem active site. Mutagenesis studies confirmed that the Met-Tyr-Trp cross-link is required for catalatic activity (Regelsberger et al, 2000;Jakopitsch et al, 2004;Ghiladi et al, 2005;Kapetanaki et al, 2007;Zhao et al, 2010Zhao et al, , 2013. These structures have provided many insights into the structure and function of KatGs.…”
Section: Introductionmentioning
confidence: 82%
“…tion, whereas the in conformation is connected with reduction of the MYW radical (39,44,45,49,53). Interestingly, a recent computational study suggests that Arg-418 facilitates the rotation of the Tyr and Trp aromatic rings with respect to one another, helping enable reduction of the MYW radical by the Fe III -O 2 .…”
Section: Proximal Tryptophan and Inactivation Of Katg Catalasementioning
confidence: 99%
“…At pH 6.5, corresponding roughly to the optimum pH for catalase activity, this arginine equally populates both conformational states (48,49). Substitution of Arg-418 with Leu, Ala, or Asn, but not Lys, sharply diminishes the catalase activity of KatG (39,49,50,52), and as has been recently shown with Magnaporthe grisea extracellular KatG, it eliminates the pH dependence of catalase activity (52). The mechanism by which Arg-418 facilitates catalatic turnover is still under investigation.…”
mentioning
confidence: 90%